2018
DOI: 10.1007/s12250-018-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

The Scorpion Venom Peptide Smp76 Inhibits Viral Infection by Regulating Type-I Interferon Response

Abstract: Dengue virus (DENV) and Zika virus (ZIKV) have spread throughout many countries in the developing world and infect millions of people every year, causing severe harm to human health and the economy. Unfortunately, there are few effective vaccines and therapies available against these viruses. Therefore, the discovery of new antiviral agents is critical. Herein, a scorpion venom peptide (Smp76) characterized from Scorpio maurus palmatus was successfully expressed and purified in Escherichia coli BL21(DE3). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The virus particles are spherical and small in size, with an envelope protein and membrane proteins. It causes microcephaly and Guillain-Barre syndrome [ 45 ].…”
Section: Main Scorpion Avps and Targeted Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…The virus particles are spherical and small in size, with an envelope protein and membrane proteins. It causes microcephaly and Guillain-Barre syndrome [ 45 ].…”
Section: Main Scorpion Avps and Targeted Virusmentioning
confidence: 99%
“…rSmp76 is able to inactivate established infection effectively with an IC 50 of 6.63 μ mol/l. rSmp76 suppresses the established infection of ZIKV by triggering interferon regulatory transcription factor 3 phosphorylation, leading to the upregulation of IFN- β expression and inhibition of viral infection [ 45 , 47 ].…”
Section: Main Scorpion Avps and Targeted Virusmentioning
confidence: 99%
“…Although the detailed molecular mechanisms of the rSmp76-induced inhibitory effects need to be elucidated, it seems that the mechanism of inhibition did not include direct inactivation of the viral particles. It has been suggested that rSmp76 suppresses an established viral infection by upregulating interferon-β expression through the phosphorylation of the interferon regulatory factor 3, which enhances type-I IFN responses and thus inhibits viral infection [131]. Since the achievement of viral clearance is very difficult, antiviral agents, such as rSmp76, that can suppress established viral infections are considered to be more efficient than traditional antiviral therapeutics, which exert their antiviral effects through the direct inactivation of viral particles or the inhibition of viral cell entry [131].…”
Section: Antiviral Effectsmentioning
confidence: 99%
“…Interestingly, the recombinant Smp76 was shown to inhibit DENV and ZIKV infections in cultured cell lines and primary mouse macrophages. However, rSmp76 did not inactivate the viral particles directly but suppressed the established viral infection by upregulating the expression of IFN-β (Ji et al 2018). This mechanism is significantly different from the virucidal effect of native Smp76 peptides.…”
Section: Lack Of Antiviral Activity Of Full-length Synthetic Smp76 Without Disulfide Bondsmentioning
confidence: 99%